Alpha-thalassemia 1 among Married Couples in Six Northeastern Provinces - Jearakul, Wipavadee; Khamsaen, Junchay (Journal of Health Science of Thailand, 2018)
The retrospective study of 1,368 cases of 684 couples from Ubon Ratchathani, Si Sa Ket, Amnat Charoen, Yasothon, Nakhon Phanom and Mukdahan provinces during June 2006 - May 2008 at clinical pathology section Regional Medical Science Center Ubon Ratchathani, was done to find out the status of alpha-thalassemia. The study reported the gestation periods of 3-40 weeks (x̅ 14.6, SD 6.9), 13-46 years old (x̅ 26.6, SD 6.8), proportions of positive OF and DCIP screening test among them were 94.9 and 61.0 percent, respectively. The husbands were 17-58 years old (x̅ 30.2, SD 7.2), and proportions of positive OF and DCIP screening test were 94.6 and 47.4 percent There were a case of THAI (0.07%) and 139 cases of SEA type of alpha-thalassemia (10.16%).